2020
DOI: 10.1155/2020/9136157
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model to Investigate the Transmission of COVID-19 in the Kingdom of Saudi Arabia

Abstract: Since the first confirmed case of SARS-CoV-2 coronavirus (COVID-19) on March 02, 2020, Saudi Arabia has not reported quite a rapid COVD-19 spread as seen in America and many European countries. Possible causes include the spread of asymptomatic COVID-19 cases. To characterize the transmission of COVID-19 in Saudi Arabia, a susceptible, exposed, symptomatic, asymptomatic, hospitalized, and recovered dynamical model was formulated, and a basic analysis of the model is presented including model positivity, bounde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…It is not difficult to write the reproduction number for the disease-free equilibrium point of Eq. ( 12 ) as [ 5 ] …”
Section: Mathematical Model and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not difficult to write the reproduction number for the disease-free equilibrium point of Eq. ( 12 ) as [ 5 ] …”
Section: Mathematical Model and Discussionmentioning
confidence: 99%
“…Regarding COVID-19, from the initial spread of COVID-19, many of the known mathematical models were used, or newly established by many researchers, For example Giordano et al in [ 4 ] proposed the so called SIDARTHE model and concluded that restrictive social-distancing measures will need to be combined with widespread testing and contact tracing to end the ongoing COVID-19 pandemic. At a same time, Alshammari [ 5 ] proposed the SEYNHR compartmental model and applied real data for Saudi Arabia and obtained good predictions on a short term. The role of quarantining and isolation to control the spread of COVID-19 is studied by Memon et al [ 6 ], where they used an extended SIR model.…”
Section: Introductionmentioning
confidence: 99%
“…The data is publicly accessible via the COVID-19 dashboard of the Saudi Ministry of Health [27]. The reason we restricted the data to this period is to be able to compare the obtained reproduction number with similar results available in the literature [30,31].…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Both the infected cases (Figure 2A) and removed cases (Figure 2B) show a reasonable quality of fit. Since the optimization task led to local optima, we were guided by the results reported in [22,30,31] in selecting initial conditions and bounds on the fitted model parameters. The optimum values of model parameters are shown in Table 2.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Since patient zero was discovered, non-confidential data of COVID-19 have been available and free to use to prompt health innovations and digital health technology applications. Many researchers have used the data to model the future of the pandemic or to predict new cases and deaths in the upcoming months [30][31][32][33][34]. Data accessibility has facilitated building models to predict the future of the pandemic in Saudi Arabia and has helped decision-makers to set plans and strategies to fight COVID-19 [35,36].…”
Section: Determinants For Optimising Dhtpsmentioning
confidence: 99%